Introduction to a common good approach to development - Nebel, Mathias (Journal of global ethics, 2025)
In this article, we introduce a common good approach to development as a necessary and transformative complement to development theory and practice. Going beyond individual assessments, we distinguish a common good approach to development as one that focuses on the processes by which societies organise themselves to produce the goods that we value collectively and that bind a society together. We argue that a common good approach to development is about the quality of the social processes and institutions (i.e. the social dynamics) that promote an ever-increasing human coexistence. We then propose a theoretical framework to operationalise such an approach through a metric of common good dynamics at the local level.